2012
DOI: 10.1007/s11695-012-0645-9
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Adjustable Gastric Banding: A 10-Year Single-Centre Experience of 575 Cases with Weight Loss Following Surgery

Abstract: In this cohort of patients, %WL and EBWL were 18.3 and 40 % ≥ 5 years after LAGB, respectively, and early and late complication rates were 2.2 and 20 %, respectively. Majority of late complications were in the first 100 patients. Multifactorial causes included the surgical learning curve and patient selection process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 26 publications
2
30
2
1
Order By: Relevance
“…Our findings were consistent with those obtained in other studies describing a long-term survey after AGB. Thus, at 10 years, the mean EWL is 32% in our study, while other studies demonstrated better results at long-term with a mean EWL from 40 to 50% [10,11,12] . The initial weight loss (48% in our study) was comparable to other studies [13] ), as its subsequent ascension is well known [14,15] .…”
Section: Discussioncontrasting
confidence: 58%
“…Our findings were consistent with those obtained in other studies describing a long-term survey after AGB. Thus, at 10 years, the mean EWL is 32% in our study, while other studies demonstrated better results at long-term with a mean EWL from 40 to 50% [10,11,12] . The initial weight loss (48% in our study) was comparable to other studies [13] ), as its subsequent ascension is well known [14,15] .…”
Section: Discussioncontrasting
confidence: 58%
“…Recently, in their 10-year single-centre experience in Sunderland, Alhamdani et al reported a median %EWL of 40% at 5 years following LAGB among their 575 patients but there was no comment on sex or ethnicity. 25 DeMaria et al reported 12% EWL and 44% EWL in AfroCaribbean and Caucasian patients respectively at three years following LAGB (p<0.05).…”
Section: Discussionmentioning
confidence: 94%
“…15 In a review from 2012, remission of diabetes mellitus was more frequent in Afro-Caribbean than in Caucasian patients following bariatric surgery although this was not statistically significant. 25 Our study did not assess resolution in co-morbidities.…”
Section: Study Limitationsmentioning
confidence: 93%
“…In all cases with slippage, frequent vomiting both caused by swallowing large portions of food or self-induced vomiting was observed. The literature reviews revealed a 1-22% of band slippages post LAGB operation [8][9][10][11][12][13][14]. Thirteen patients were managed conservatively by complete emptying of the gastric band while prescribing Proton Pump Inhibitors simultaneously for about 12 weeks.…”
Section: Discussionmentioning
confidence: 99%